2004
DOI: 10.1002/cjce.5450820405
|View full text |Cite
|
Sign up to set email alerts
|

Fines/Water Interactions and Consequences of the Presence of Degraded Illite on Oil Sands Extractability

Abstract: The chemical composition of the aqueous phase in oil sand slurries influences bitumen recovery from oil sands, especially those containing greater than 10% fines. The composition is controlled by a combination of mixing and dilution, ion exchange with clay surfaces and precipitation of divalent ions as carbonate minerals. Elevated levels of soluble potassium in the oil sand, which appear to be a marker for degraded illite or smectitic clays, are associated with depressed bitumen recovery. These clays have a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 12 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…Former studies (Abend and Lagaly, 2000;Amorós et al, 2002;Mpofu et al, 2003;Rasteiro and Salgueiros, 2005;McFarlane et al, 2006;Faers et al, 2006) showed the effect of solution chemistry on the rheological behaviour of solid dispersions. With reference to the oil sands extraction process, Wallace et al (2004) showed the impact of aqueous phase composition on bitumen recovery in the presence of fine solids. All samples in this study were prepared in supernatant water separated from centrifuged MFT.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies (Abend and Lagaly, 2000;Amorós et al, 2002;Mpofu et al, 2003;Rasteiro and Salgueiros, 2005;McFarlane et al, 2006;Faers et al, 2006) showed the effect of solution chemistry on the rheological behaviour of solid dispersions. With reference to the oil sands extraction process, Wallace et al (2004) showed the impact of aqueous phase composition on bitumen recovery in the presence of fine solids. All samples in this study were prepared in supernatant water separated from centrifuged MFT.…”
Section: Introductionmentioning
confidence: 99%
“…18,24 Using AFM to study the interaction potential between bitumen and clays (montmorillonite and kaolinite) in the presence of calcium, Liu et al 12 measured a stronger adhesion force (four times greater) between bitumen and montmorillonite than between bitumen and kaolinite. The same technique was applied to study the interactions between bitumen and real mineral fines recovered from good and poor processing ores.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[16][17][18] The negative effects of clay minerals on bitumen extraction from the oil sands have been reported by several researchers. [5,6,[17][18][19][20][21][22] In addition, Omotoso and Mikula [5] have also suggested that the presence of Fe (oxyhydr)oxides with high surface area may have negative consequences on bitumen extractability from the oil sands. Hence, the mineral and chemical characterisation of the four petrologic end members are crucial for better understanding of the mineralogical and geochemical factors affecting aqueous or nonaqueous bitumen extraction and solvent recovery from the extraction tailings.…”
Section: Introductionmentioning
confidence: 99%